Selexipag for the Treatment of Pulmonary Arterial Hypertension - Sitbon, Olivier; Channick, Richard; Chin, Kelly M; Frey, Aline; Gaine, Sean; Galiè, Nazzareno; Ghofrani, Hossein-Ardeschir; Hoeper, Marius M; Lang, Irene M; Preiss, Ralph; Rubin, Lewis J; Di Scala, Lilla; et al. (The New England journal of medicine, 2015)
Among over 1100 patients with pulmonary arterial hypertension who received selexipag, an oral selective IP prostacyclin-receptor agonist, or placebo, the risk of the composite end point of death or complication was lower with selexipag than with placebo at 1.3 years of follow-up. Pulmonary arterial hypertension is a severe disease with a poor prognosis despite available treatment options. 1 Current recommendations support the use of a combination of therapies that target the endothelin, nitric-oxide, and prostacyclin pathways. 2 , 3 Despite the benefits of intravenous prostacyclin therapy, 2 , 4 many patients with pulmonary arterial hypertension die without ever receiving this treatment. 5 , 6 The burden and risks related to the administration of prostacyclin therapy are probably contributing factors. 7 Selexipag is an oral selective IP prostacyclin-receptor agonist that is structurally distinct from prostacyclin. 8 – 11 In a placebo-controlled, phase 2 trial involving patients who were already receiving treatment for pulmonary . . .